The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution IV. Family Andrenidae, genus Andrena Fabricius, 1775, species described by F. Morawitz - Astafurova, Yulia V.; Proshchalykin, Maxim Yu.; Sidorov, Dmitry A.; Osytshnjuk, Anna Z. (Zootaxa, 2021)
The type specimens for names of bee taxa in the genus Andrena Fabricius, 1775 of family Andrenidae described by F. Morawitz and deposited in the Zoological Institute, Russian Academy of Sciences (St. Petersburg) are reviewed. Name-bearing types of 68 species are illustrated and detailed information is provided. Lectotypes are designated here for the following 32 nominal taxa: Andrena adjacens Morawitz, 1875, A. anthracina Morawitz, 1880, A. atrohirta Morawitz, 1893, A. croceiventris Morawitz, 1871, A. ehnbergi Morawitz, 1888, A. formosa Morawitz, 1877, A. glasunowi Morawitz, 1894, A. inconspicua Morawitz, 1871, A. laticeps Morawitz, 1877, A. melanura Morawitz, 1877, A. mongolica Morawitz, 1880, A. mucronata Morawitz, 1871, A. nigrobarbata Morawitz, 1871, A. nylanderi Morawitz, 1865, A. ochracea Morawitz, 1872, A. opaca Morawitz, 1868, A. orbitalis Morawitz, 1871, A. paliuri Morawitz, 1877, A. pretiosa Morawitz, 1893, A. ranunculorum Morawitz, 1877, A. rotundilabris Morawitz, 1877, A. sahlbergi Morawitz, 1888, A. salicina Morawitz, 1877, A. schencki Morawitz, 1866, A. semirubra Morawitz, 1875, A. sexguttata Morawitz, 1877, A. sylvatica Morawitz, 1877, A. transitoria Morawitz, 1871, A. truncatilabris Morawitz, 1877, A. tscheki Morawitz, 1872, A. virago Morawitz, 1894, A. curiosa Morawitz, 1877.